Isolation and identification of possible analgesics and antihypertensive agents from antidesma venosum - Mashimbye, Mahlori Jeffrey (Rhodes University, Faculty of Science, Department of Chemistry and Biochemistry, 1986)
This investigation originated from a suggestion by Noristan Laboratories, Pretoria, that because Black people were using the roots of A. venosum E. MEY. ex. TUL for treating headache, the plant might contain analgesics. No previous chemical investigation has been carried out on this plant but from previous work done on other species antihypertensive agents were expected to be present
Keywords: Antidesma; Analgesics; Hypotensive agents